Evaluasi Program Bantuan Saran Hunian Pariwisata (Homestay) di Desa Nampar Macing Kabupaten Manggarai Barat - Maria Kristiana Yuniar; Alfred O. Ena Mau; Rouwland A. Benyamin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Sarhunta assistance is government financial support for communities in the delineation of handling locations to improve the quality of houses, residential development for business functions, and environmental arrangements to support tourism or economic development. One form of activity is to provide tourism residential facilities (homestay) while improving the quality of settlements that meet the requirements of livable homes. The purpose of this study was to Evaluation of Sarana Hunian Pariwisata (Homestay) Assistance Program in Nampar Macing Village, West Manggarai Regency. The method used in this research is descriptive qualitative. The results showed that the utilization of Sarhunta as a business function in Nampar Macing Village, Manggarai Regency is not yet optimal. The lack of community understanding and the absence of technical guidance are factors in the failure of Sarhunta utilization.